Odpowiedzi

2010-03-03T09:07:18+01:00
A) 1.8-8x/1.2 - 1.3-3x/2= 5x-0.4/0.3
1,8-8x:(12/10)-1,3-1,5x=5x-(4/10):(3/10)
1,8-1,3-8x*(10/12)-1,5x=5x-(4/10)*(10/3)
0,5-8x*(5/6)-1,5x=5x-(4/3)
0,5-(20/3)x-(15/10)x=5x-(4/3)
(5/10)-(3 i 2/3)x-(3/2)x=5x-(1 i 1/3)
(1/2)-(3 i 2/3)x-(1 i 1/2)x=5x-(1 i 1/3)
(3/6)-(3 i 20/30)x-(1 i 15/30)x=5x-(1 i 2/6)
(3/6)-(4 i 35/30)x=5x-(1 i 2/6)
(3/6)-(5 i 5/30)x=5x-(1 i 2/6) /+(1 i 2/6)
(1 i 5/6)-(5 i 1/6)x=5x /+(5 i 1/6)x
(1 i 5/6)=(10 i 1/6)x
(11/6)=(61/6)x /:(61/6)
(11/6)*(6/61)=x
x=(11/61)

b)3(1.2-x)/10 - 5+7x/4 = x + 9x+0.2/20 -4(13x-0.6)/5
(3,6-3x)/10-5+1,75x=10x+4-(52x-2,4)/5
0,36-0,3x-5+1,75x=10x+4-10,4x+0,48
-4,64+1,45x=-0,4x+4,48 /+0,4x
-4,64+1,85x=4,48 /+4,64
1,85x=9,12 /:1,85
x=4,9 (w przybliżeniu!)
2010-03-03T09:30:16+01:00